Atypical location of Coumel Tachycardia in Adult: Case Report - de Castro Galvão, Raoni; Velasco Pucci, João Paulo; Gomes Vieira, Ofir (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Coumel Tachycardia or Incessant Junctional Reentrant (IJRT) generally affects the infant-juvenile population and is characterized by tachycardia due to atrioventricular reentry (AV) mediated by an exclusive, slow, decremental retrograde conduction pathway mostly located in the posterosseptal region of the tricuspid ring. Case report: The present study reported the case of an adult, 49 years old, with IJRT of atypical location. The patient reported feeling palpitations for 5 years with worsening in the last 6 months. After one of his seizures, an electrocardiogram (ECG) documented tachycardia due to AV reentry with a long RP ‘interval. Subjected to an electrophysiological study, an accessory pathway of exclusive retrograde conduction with decreasing characteristics was observed, located in the right mid-septal region. There was easy induction of IJRT, remaining sustained throughout the study. A radiofrequency ablation was performed in the mid-septal D region with interruption of tachycardia, with no more atrioventricular retrograde conduction, the procedure ended without complications. Discussion: Interestingly, the case described differs both in terms of the age range of the most frequent involvement of the IJRT (children and young people), as well as the most common location of the accessory pathway (posterior and postero-septal region of the tricuspid ring). Ablation proved to be effective in this case and is the treatment of choice for IJRT despite the anomalous location of the accessory pathway (Middle-septal D: described in bibliographic reviews in only 7% of IJRT cases) and a potentially dangerous region due to proximity to the trunk of the His beam.